2002
DOI: 10.1128/cdli.9.2.299-307.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and Prospective Study of Different Immune Parameters in Healthy Subjects at Risk for Tuberculosis and in Tuberculosis Patients

Abstract: It has not been fully elucidated which of the components of the immune response against Mycobacterium tuberculosis is indicative of resistance or susceptibility. The aim of this study was to identify an immune parameter that could be indicative of either resistance or susceptibility to M. tuberculosis infection. We prospectively studied (three determinations, at months 0, 8, and 12) 15 patients with chronic pulmonary tuberculosis and 42 healthy individuals with a recent and frequent contact with tuberculosis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
15
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
6
15
0
1
Order By: Relevance
“…The mean values for the expression of CD69 in groups of patients with clinically inactive TB and healthy individuals with a positive TST reaction were, however, lower. The highest levels of IFN-␥ in our study, as well as in previous (8,26,32,37,38), were observed in the group of healthy individuals with a positive TST reaction and patients with clinically inactive TB. The mean levels of IFN-␥ secreted by the group of patients with culture-proven active TB before treatment were lower.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The mean values for the expression of CD69 in groups of patients with clinically inactive TB and healthy individuals with a positive TST reaction were, however, lower. The highest levels of IFN-␥ in our study, as well as in previous (8,26,32,37,38), were observed in the group of healthy individuals with a positive TST reaction and patients with clinically inactive TB. The mean levels of IFN-␥ secreted by the group of patients with culture-proven active TB before treatment were lower.…”
Section: Discussionsupporting
confidence: 70%
“…The expression of the early lymphocyte activation marker CD69 after stimulation with tuberculin has been evaluated in healthy individuals with positive and negative TST results and has been shown to correlate well with the TST induration diameter (30). A significantly higher level of expression of CD69 was found in patients with TB 8 months after they started treatment compared to that in healthy controls (26). Furthermore, in patients coinfected with HIV type 1 and M. tuberculosis, the expression of CD69 correlated with the results of TST and IFN-␥ production in PPD-stimulated CD4 T lymphocytes (15).…”
mentioning
confidence: 93%
“…In this study, there was also no significant difference in the secretion of IL-10 by PBMCs from household contacts with or without a history of TB. Similarly, another study showed that patients with chronic TB and healthy communicants presented IL-10 levels that did not allow discrimination between individuals with susceptibility or resistance to TB (21). This finding suggested that T memory cells circulated and responded in the same way in individuals who had been exposed to the same source of mycobacterium, independent of their susceptibility toward developing TB.…”
Section: Discussionmentioning
confidence: 99%
“…The TST is widely used for the diagnosis of M. tuberculosis infection but has several drawbacks such as cross-reactivity, poor specificity, limited sensitivity, and the need for a followup visit limits its reliability (10,12,20,21). In the past few years, in vitro tests of cell-mediated immunity, in particular LPA and IFN-␥ detection in the supernatant of stimulated cultures, have been used for diagnosing TB (12,13,32,33). However, these assays exhibited a low specificity due to the cross-reactivity of the Ags used (whole protein extracts or the 30-kDa Ag of M. tuberculosis, BCG, and PPD).…”
Section: Discussionmentioning
confidence: 99%